The cytochrome P450 isoenzyme and some new opportunities for the prediction of negative drug interaction in vivo - Sychev DA; Ashraf GM; Svistunov AA; Maksimov ML; Tarasov VV; Chubarev VN; Otdelenov VA; Denisenko NP; Barreto GE; Aliev G (Dove Medical Press, 2018)
Dmitrij A Sychev,1 Ghulam Md Ashraf,2 Andrey A Svistunov,3 Maksim L Maksimov,4 Vadim V Tarasov,3 Vladimir N Chubarev,3 Vitalij A Otdelenov,1 Natal’ja P Denisenko,1 George E Barreto,5,6 Gjumrakch Aliev7–9 1Russian Medical Academy of Postgraduate Education Studies, Moscow, Russia; 2King Fahd Medical Research Center, King Abdulaziz University, Jeddah, Saudi Arabia; 3Sechenov First Moscow State Medical University, Moscow, Russia; 4Branch Campus of the Federal State Budgetary Educational Institution of Further Professional Education «Russian Medical Academy of Continuous Professional Education» of the Ministry of Healthcare of the Russian Federation, Kazan State Medical Academy, Volga Region, Kazan, Russia; 5Departamento de Nutrición y Bioquímica, Facultad de Ciencias, Pontificia Universidad Javeriana, Bogotá D.C., Colombia; 6Instituto de Ciencias Biomédicas, Universidad Autónoma de Chile, Santiago, Chile; 7GALLY International Biomedical Research Consulting LLC, San Antonio, TX, USA; 8School of Health Science and Healthcare Administration, University of Atlanta, Johns Creek, GA, USA; 9Institute of Physiologically Active Compounds Russian Academy of Sciences, Chernogolovka, Russia Abstract: Cytochrome (CYP) 450 isoenzymes are the basic enzymes involved in Phase I biotransformation. The most important role in biotransformation belongs to CYP3A4, CYP2D6, CYP2C9, CYP2C19 and CYP1A2. Inhibition and induction of CYP isoenzymes caused by drugs are important and clinically relevant pharmacokinetic mechanisms of drug interaction. Investigation of the activity of CYP isoenzymes by using phenotyping methods (such as the determination of the concentration of specific substrates and metabolites in biological fluids) during drug administration provides the prediction of negative side effects caused by drug interaction. In clinical practice, the process of phenotyping of CYP isoenzymes and some endogenous substrates in the ratio of cortisol to 6β-hydroxycortisol in urine for the evaluation of CYP3A4 activity has been deemed to be a quite promising, safe and minimally invasive method for patients nowadays. Keywords: cytochrome CYP450, drug interaction, drug metabolism, phenotyping